PENDEKATAN MODEL EVALUASI PEMBELAJARAN PENDIDIKAN ISLAM - Syukralaili, Syukralaili; Fauzi, Muhammad; Ermiza, Ermiza; Nurhayani, Nurhayani; Jayusman, Sandi; Putra, Aria; Lahmi, Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Learning evaluation is an essential component of the educational process, including in Islamic education, which is characterized by a holistic and transcendental value orientation. Evaluation in Islamic education is not merely intended to measure students’ academic achievement, but also to assess the learning process and the internalization of faith, moral values, and Islamic behavior in students’ daily lives. This article aims to examine the concept of learning evaluation in Islamic education, its philosophical and theological foundations, as well as various approaches and evaluation models that are relevant to the context of Islamic education. This study employs a qualitative approach with a descriptive research design based on library research. The data sources include the Qur’an and Hadith, classical and contemporary literature on Islamic education, and relevant national and international journal articles on learning evaluation. Data were analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that learning evaluation in Islamic education is integrative in nature, encompassing cognitive, affective, and psychomotor domains, and is grounded in the principles of muhasabah, justice, honesty, and responsibility. The evaluation approaches include cognitive, affective, psychomotor, and holistic-integrative approaches. Relevant evaluation models include the CIPP model, the Kirkpatrick model, and evaluation models based on Islamic values. Learning evaluation in Islamic education functions not only as a tool for measuring learning outcomes but also as a means of character development and strengthening students’ faith toward the formation of insan kamil.Keywords: learning evaluation, Islamic education, evaluation models, evaluation approaches, insan kamil